Negotiating Worlds, Words and Identities: Scaffolded literacies for pre-service teachers and children - Cumming-Potvin, Wendy (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2012)
Aiming to extend sociocultural theory about the teaching and learning of literacies, this article reports on data from a qualitative study underpinned by a sociocultural framework (Rogoff, 1990; Vygotsky, 1986). Conducted in an Australian university community, the project tracked a group of pre-service teachers engaging in scaffolded literacy events, such as face-to-face and on-line discussions and shared reading experiences with children. Highlighting the importance of examining the teaching and learning of literacies across formal and informal settings, results offer information about how these pre-service teachers constructed understandings and situated identities (Gee, 1990, 2000-2001) through scaffolding. Pedagogical implications for pre-service teacher education are discussed.